Prevalence and characteristics of e-cigarette users among Malaysian current and ex-smokers - Ho, Bee Kiau; Nik Mohamed, Mohamad Haniki; Ab Rahman, Jamalludin; Draman, Samsul; Kartiwi, Mira; Ab Rahman, Norny Syafinaz; Md Haris Robson, Noor Zurani; Chan, Caryn Mei Hsien; Lim, Kuang Hock; Baharom, Nizam; Ismail, Norliana; Tee, Guat Hiong; et al. (Academy of Family Physicians of Malaysia, 2019)
Introduction: Electronic cigarettes (ECs) are new devices that have been accepted widely by both smokers and non-smokers. However, the evidence on EC used in Malaysia is scarce. The objective of this study was to determine the prevalence of EC use and the socio-demographic and smoking characteristics associated with current EC use among Malaysian current and ex-smokers. Methods: This was a sub-analysis of data from a cross-sectional, national-population- based EC study conducted from May to June in 2016 in Malaysia. A detailed description of the sampling methods can be found in the National E-cigarette Survey (NECS) 2016 report. Briefly, data were obtained from 1396 individuals who had ever been smokers, i.e., 957 (68.6%) current smokers and 439 (31.4%) ex-smokers. Results: Current EC use was found predominantly among current smokers (8.0%) as compared with ex-smokers (4.3%). Among current smokers, the main reasons given for smoking ECs were wanting to try it (44.7%), followed by intention to quit tobacco smoking (15.8%) and to reduce tobacco smoking (10.5%). Using multiple logistic regression analysis, we found that among current smokers, current EC users were more likely to be younger, i.e., 18-44 years (aOR= 4.83, 95% CI= 1.97-11.86, p=0.001), urban residents (aOR= 1.89, 95% CI= 1.15-3.11, p=0.012), single/ divorced/ widowed (aOR= 2.11, 95% CI= 1.24-3.61, p=0.006) and students (aOR= 2.25, 95% CI= 1.01-5.01, p=0.048). Among ex- smokers, only younger respondents (18-44 years old) was reported as being more likely to be current EC users (aOR= 3.81, 95% CI= 1.14-12.76, p=0.030). Conclusion: This study showed that currently using and ever having used ECs were more prevalent among current smokers. The reasons given for initiating EC use among current smokers were mainly wanting to try it, followed by intention to quit and to reduce tobacco smoking. Current EC use appears to be common among current smokers who are younger, urban residents, single/divorced/widowed and students. Therefore, EC cessation intervention strategies and policies should target these high-prevalence groups.